The effects of acute and repeated methylenedioxypyrovalerone (MDPV) administration on striatal transcriptome networks in male long evans rats. (1st November 2019) - Martyniuk, Christopher J.; Pompilus, Marjory; Schmidt, Jordan; Duncan, Allison; Febo, Marcelo
Highlights: Methylenedioxypyrovalerone (MDPV) is a cathinone derivate and drug of abuse. Rats were injected with either saline or MDPV (1 mg/kg) (single or repeated dose). MDPV increased locomotor and stereotyped activity. Gene networks associated with synaptic transmission were altered by MDPV. Abstract: The psychoactive drug methylenedioxypyrovalerone (MDPV) elicits feelings of euphoria and hyperexcitability, but can also result in paranoia, agitation, and depression by unknown mechanisms. We identified molecular networks in the rat striatum that were affected by single or repeated exposure to MDPV. Male Long Evans rats were injected with either saline or MDPV (1 mg/kg) (single or repeated MDPV) over 5 days. To distinguish the effects of repeated MDPV from a single exposure, an additional group received saline over 4 days and then MDPV on the 5th day. Twenty-four hours after the final injection, the left dorsal striatum was processed for transcriptomics. The transcriptome response was subtle after 24 h, and a single gene passed an FDR correction (LOC103691845) following repeated MDPV treatment. Gene set and subnetwork enrichment analyses were conducted to improve data interpretation from a network perspective. Consistent with the mode of action of MDPV, networks related to the nigrostriatal dopaminergic system were altered in the rat striatum. Transcriptional networks related to cognition, short and long-term memory, and synaptic transmission were over-represented in the striatum of rats repeatedly injected with MDPV. This study identifies potential transcriptional networks altered by single or repeated MDPV exposure, which can be interrogated further to elucidate molecular mechanisms underlying cathinone abuse.